Barbora Markéta Eliášová: Nippon as the Second Home. The First Czech Women ́s Traveller, her Life and Literary Work (Theatrum historiae, 2010)
The work is dedicated to the first Czech independent traveler Barbora Markéta Eliášová. The author tries to describe her fruitful and interesting life. As an orphan and poor village child, she made her dream come true and she became a teacher. After that she decided to concentrate to go and search for the luck far away in Japan. She found a second home there and she came back really very glad. Those journeys to Japan were prolonged with thirteen-moths traveling trip via Java, Bali, Australia and South Africa. Upon the experiences she had, she also wrote several travel books. The author is introducing the travel books from her fourth journey to Japan, as well as the overview of her literary work, newspapers articles, magazine articles and belles letters for youth that she worked on after her active traveling years until she died.